2015
DOI: 10.1103/physrevd.92.125007
|View full text |Cite
|
Sign up to set email alerts
|

Derivative expansion for the electromagnetic Casimir free energy at high temperatures

Abstract: We study the contribution of the thermal zero modes to the Casimir free energy, in the case of a fluctuating electromagnetic (EM) field in the presence of real materials described by frequencydependent, local and isotropic permittivity ( ) and permeability (µ) functions.Those zero modes, present at any finite temperature, become dominant at high temperatures, since the theory is dimensionally reduced. Our work, within the context of the Derivative Expansion (DE) approach, focusses on the emergence of non analy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Working out the NTLO correction to PFA for these two models is of great interest, because in the HT limit the perturbative kernels for N and P bc display a singular be-havior for small in-plane momenta, invalidating the DE [19, 28] [42]. The DE has been shown to fail also for the plasma model in the HT limit in [37]. As a result, the analytic form of the NTLO for N and P bc is so far unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Working out the NTLO correction to PFA for these two models is of great interest, because in the HT limit the perturbative kernels for N and P bc display a singular be-havior for small in-plane momenta, invalidating the DE [19, 28] [42]. The DE has been shown to fail also for the plasma model in the HT limit in [37]. As a result, the analytic form of the NTLO for N and P bc is so far unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The high temperature (classical) limit is dominated, for a Bose field, by the n = 0 Matsubara mode. In a previous work [5], we have shown that the zero mode free energy can be written as…”
Section: Free Energy For the Electromagnetic Fieldmentioning
confidence: 99%
“…Its application to compact objects like the sphere thus relies on the assumption that only the lower hemisphere contributes when R/L 1 [32]. Moreover, the derivative expansion requires analyticity of the perturbative kernel, a condition not met for the zero-frequency contribution when taking the plasma model [33].…”
mentioning
confidence: 99%